Pandoraea sp. B-6 assists the deep eutectic solvent pretreatment of rice straw via promoting lignin depolymerization. (June 2018) - Liu, Dan; Yan, Xu; Zhuo, Shengnan; Si, Mengying; Liu, Mingren; Wang, Sheng; Ren, Lili; Chai, Liyuan; Shi, Yan
Highlights: Pandoraea sp. B-6 assisted DES pretreatment of RS was developed. Lignin depolymerization was enhanced by Pandoraea sp. B-6. RS digestibility was increased by 0.9–3.1 times compared to untreated RS. The role of Pandoraea sp. B-6 in pretreatment was explained by a cornhusking model. Abstract: Lignin depolymerization is a challenging process in biorefinery due to the recalcitrant and complex structure of lignin. This challenge was herein addressed via elaborating a new strategy of combining the bacterial strain Pandoraea sp. B-6 (hereafter B-6) with a deep eutectic solvent (DES) to pretreat rice straw (RS). In this approach, DES effectively depolymerized lignin yet easily caused sugar loss under severe conditions. B-6 not only overcame the obstacle of lignin droplets, but also significantly improved enzymatic digestibility. After B-6 assisted DES pretreatment, the reducing sugar yield increases by 0.3–1.5 times over DES pretreatment and 0.9–3.1 times over the untreated RS. Furthermore, a "cornhusking" mechanism explaining the improvement of the enzymatic digestibility by B-6 was suggested based on physicochemical characterizations of the untreated and pretreated RS. The findings provided a comprehensive perspective to establish a DES−microbial process for lignocellulose pretreatment.